2016
DOI: 10.1002/sca.21313
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and nanomechanical changes in mechanosensitive endothelial cells induced by colloidal AFM probes

Abstract: Mechanotransduction is one of the main properties of endothelial cells (ECs) phenotype. Hemodynamic forces like flow-generated endothelial shear stress play a fundamental role in ECs cytoskeletal remodeling and activate signaling cascades in ECs. AFM methods are widely used to characterize morphology as well as mechanical properties of cells. In both cases AFM probes directly interact with cell surface exerting mechanical forces on the cellular membrane, which in turn may stimulate mechanosensitive receptors p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…For the control db/+ mice, the age-averaged value of the endothelium elastic modulus was E EC = 862 ± 16 Pa. This value is in agreement with the modulus value of the cytoplasm in endothelial cells measured in a glass microplate compression experiment 56 and with our previous in vitro studies 61 . For db/db mice, we observed a significant increase in the age-averaged value of the endothelium elastic modulus to 1449 ± 18 Pa. Our recent in vitro study revealed similar changes for EA.hy926 endothelial cells in response to chronic hyperglycaemia 31 .…”
Section: Discussionsupporting
confidence: 89%
“…For the control db/+ mice, the age-averaged value of the endothelium elastic modulus was E EC = 862 ± 16 Pa. This value is in agreement with the modulus value of the cytoplasm in endothelial cells measured in a glass microplate compression experiment 56 and with our previous in vitro studies 61 . For db/db mice, we observed a significant increase in the age-averaged value of the endothelium elastic modulus to 1449 ± 18 Pa. Our recent in vitro study revealed similar changes for EA.hy926 endothelial cells in response to chronic hyperglycaemia 31 .…”
Section: Discussionsupporting
confidence: 89%
“…However, in situ AFM studies on fresh and vital liver tissue biopsies will be more likely in the near future—i.e., similar to the AFM studies reported on breast biopsies—as this might bridge the gap between our present in vitro observations and in vivo observations. In case of future shear stress studies, it has been found using AFM that the endothelium presented different morphologies and nanomechanical properties when shear stress or hydrostatic pressure was applied. It is likely, therefore, that the number and dynamics of fenestrae could be affected by such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The migration of cells remains random and does not depend on the direction of scanning. In another report, it was shown that continuous scanning in contact mode AFM resulted in an endothelial cell's remodelling and orientation in the scanning direction (Targosz-Korecka et al 2016). In QI mode, the contact time between the tip and the cell is vastly reduced and the loading force 2-3 times smaller than in the mentioned report.…”
Section: -D Atomic Force Spectroscopy: Elasticity As a Parameter Desmentioning
confidence: 85%